Associations of GATA4 genetic mutations with the risk of congenital heart disease: A meta-analysis. Issue 18 (May 2017) - Zhang, Yanwei; Ai, Feng; Zheng, Jiayong; Peng, Bangtian
Abstract: Background: GATA4 gene is a cardiac transcriptional factor playing important role in cardiac formation and development. Three GATA4 gene mutations, 99 G>T, 487 C>T, and 354 A>C, have been reported in congenital heart disease (CHD). Therefore, a meta-analysis was performed to explore the associations between 99 G>T, 487 C>T, or 354 A>C mutations and the risk of CHD. Methods: We searched the relevant studies in electronic databases, including ISI Science Citation Index, Embase, PubMed, CNKI, and Wan fang, from January 2006 to March 2016. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to estimate the associations between 99 G>T, 487 C>T, or 354 A>C mutations and the risk of CHD. Results: A total of 11 studies including 2878 CHD cases and 3339 controls were evaluated. There was no significant association between GATA4 99 G>T (OR = 1.22, 95% CI = 0.74–2.01, P = .43) or 487 C>T (OR = 1.16, 95% CI = 0.48–2.78, P = .74) mutations and the risk of CHD, whereas GATA4 354 A>C (OR = 1.49, 95% CI = 1.15–1.93, P = .003) mutation was significantly associated with CHD risk. Subgroup analysis was further performed for GATA4 99 G>T, 487 C>T, and 354 A>C mutations based on sample size and ethnicity, and no significant association between GATA4 99 G>T or 487 C>T mutations and the risk of CHD was found in all subgroups, whereas GATA4 354 A>C mutation was significantly associated with CHD risk in large-sample-size and Asian subgroups. However, subgroup analysis by types of CHD indicated that there was no significant association between GATA4 354 A>C mutation and the risk of ventricular septal defects. Conclusions: Our findings suggested that GATA4 99 G>T and 487 C>T mutations may not be related to the incidence of CHD. However, GATA4 354 A>C mutation was significantly associated with CHD risk.